Fostering Health Education With a Serious Game in Children With Asthma: Pilot Studies for Assessing Learning Efficacy and Automatized Learning Personalization - Delmas, Alexandra; Clement, Benjamin; Oudeyer, Pierre-Yves; Sauzéon, Helène (Frontiers in Education, 2018)
Coupled with Health Education programs, an e-learning platform – KidBreath – was participatory designed and assessed in situ (Study 1) and was augmented and tested with an Intelligent Tutoring System (ITS) based on Multi-Armed Bandit Methods (Study 2). For each study, the impact of KidBreath practice was assessed in children with asthma in terms of pedagogical efficacy (knowledge of the illness), pedagogical efficiency (usability, type of motivation and level of interest elicited) and therapeutic effect (illness perception, system’s expectation and judgement in disease self-management, child’s implication in study). For the Study 1, asthma children aged 8 to 11 years used the tool at home without time pressure for two months according to a predefined learning sequence defined by the research team. Results supported pedagogical efficacy of KidBreath, with a significant increase of general knowledge about asthma after use. It also featured a greater learning gain for children knowing the least about the illness before use. Results on pedagogical efficiency revealed a great intrinsic motivation elicited by KidBreath showing a deep level of interest in the edutainment activities. Study 2 explored an augmented version of KidBreath with learning optimization algorithm (called ZPDES) after its use during one month. Pedagogical efficacy was less conclusive than Study 1 because less content was displayed due to algorithm parameters. However, the ITS-augmented KidBreath use showed a strong impact in pedagogical efficiency and therapeutic adherence features. Even if implementation improvements must be done in future works, this preliminary study highlighted the viability of our methods to design an ITS as serious game in health education context for all chronic diseases.